Hubungan Pengalaman, Sosial Budaya Dan Sumber Informasi Terhadap Pengetahuan Ibu Hamil Mengenai Tanda Bahaya Kehamilan Di BPM Onih Marpuah Kota Depok : The Relationship between Experience, Social Culture, and Information Sources on Pregnant Women's Knowledge Regarding Danger Signs of Pregnancy at BPM Onih Marpuah, Depok City - Rukmanawati, Baeti Ida (Dohara POAJ, 2024)
Introduction: Knowledge of pregnant women about danger signs is very important for the early detection of danger signs of pregnancy. The low knowledge of mothers in recognizing dangerous signs of pregnancy results in underutilization of the referral system. One of the reasons for the delay in access to health services is the inability of pregnant women to recognize the condition of their pregnancy. Methods: The purpose of this study was to determine the relationship between experience, socio-culture, and sources of information on the knowledge of pregnant women about the danger signs of pregnancy at BPM Onih Marpuah Depok City in 2021. The sampling technique used was total sampling with a sample of 52 pregnant women. The dependent variable in this study is the knowledge of pregnant women, while the independent variable in this research is experience, sociocultural, and sources of information. The instrument in this study used a questionnaire that had been made and tested and the results were reliable. Results: The results of this study indicate that there is no relationship between experience and knowledge of pregnant women about the danger signs of pregnancy (p = 0.224), there is a sociocultural relationship to the knowledge of pregnant women about pregnancy danger signs (p = 0.021), there is a relationship between sources of information and maternal knowledge. pregnancy regarding the danger signs of pregnancy (p = 0.047). Discussion: Suggestions for BPM to increase the empowerment of pregnant women by forming classes for pregnant women and further increasing education for pregnant women about the danger signs of pregnancy so that pregnant women can carry out early detection of pregnancy danger signs.